Analysis of Climate Trends and Leading Modes of Climate Variability for MENA Region. Issue 23 (4th December 2018) - Dogar, Muhammad Mubashar; Sato, Tomonori
Abstract: The Middle East and North Africa (MENA), primarily the Arabian Peninsula (AP), is a region where the rate of mean surface temperature rise per decade is among the highest globally known during the recent past. Moreover, MENA regional climate is very sensitive to internal and external climate drivers. Therefore, it is of significant practical importance to analyze MENA sensitivity to climate trends as well as leading variability modes such as El Niño Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), and Indian summer monsoon (ISM). Using multiple regression technique on observations and the high‐resolution atmospheric model output, this study investigates the role of climate trends and leading circulation modes such as NAO, ENSO, and ISM in inducing temperature and precipitation variability in MENA region for the period 1979–2008. Our results show substantial regional temperature and precipitation responses of ENSO, NAO, and ISM over MENA. Both the model and the observations indicate that positive phase of NAO and ENSO significantly cools central parts of MENA, in particular, the AP in winter. However, in boreal summer, the warm ENSO phase produces significant warming and drying over the tropical region. The strengthening (weakening) of ISM suggests cooling (warming) and wetting (drying) over MENA rain‐belt region. Moreover, ISM induces a dipole precipitation structure over the tropics caused by Intertropical Convergence Zone shift and associated cloud distribution. High‐resolution atmospheric model slightly underestimates NAO and ENSO winter cooling over the AP; however, overall patterns are well reproduced. The conducted analysis sheds light on the internal mechanisms of MENA climate variability. Key Points: MENA region is very sensitive to the changes induced by the internal and external climate forcings This paper focuses on the importance of trend in data and leading climate modes that play significant role in shaping MENA climate Both the model and the observations indicate that positive phase of NAO and ENSO significantly cools central parts of MENA in winter